Capillary isotachophoresis with electrospray-ionization mass-spectrometric detection: Cationic electrolyte systems in the medium-alkaline range for selective analysis of medium strong bases - Malá, Zdena; Gebauer, Petr (Journal of chromatography. A, Including electrophoresis and other separation methods, 2020)
This work extends the present working range of isotachophoresis (ITP) with electrospray-ionization mass-spectrometric (ESI-MS) detection and describes for the first time a functional cationic electrolyte system for analyses at medium-alkaline pH. So far no ITP-MS application was published on the analysis of medium strong bases although there is a broad spectrum of potential analytes like biogenic amines, alkaloids or drugs, where this technique promises interesting gains in both sensitivity and specificity. The presented results include a selection of suitable sufficiently volatile ESI-compatible system components, discussion of factors affecting system properties, and recommendations for functional ITP electrolyte systems. Theoretical conclusions based on calculations and computer simulations are confirmed by experiments with a model mixture of beta-blockers. Practical applicability of the method is demonstrated on the example of analysis of sotalol in dried blood spots where direct injection of aqueous extract, ITP stacking and MS detection provide a fast, simple and sensitive technique with limits of quantitation on the sub-nM level.
Keywords: sotalol; hmotnostní spektrometrie s elektrosprejovou ionizací; kationty; elektrolyty; Electrolytes; Adrenergic beta-Antagonists; izotachoforéza; Isotachophoresis; beta blokátory; Cations; koncentrace vodíkových iontů; Spectrometry, Mass, Electrospray Ionization; Hydrogen-Ion Concentration; Sotalol